Treatment outcome of supervised exercise, home exercise and bite splint therapy, respectively, in patients with symptomatic disc displacement with reduction: A randomised clinical trial - Wänman, Anders; Marklund, Susanna (Journal of oral rehabilitation, 2020)
The best treatment strategy for disturbing temporomandibular clicking sounds is not known. The aim was to evaluate the effect of exercise and bite splint therapy, respectively, in patients with symptomatic disc displacement with reduction. The study was a randomised clinical trial of subjects with temporomandibular joint (TMJ) clicking sounds with a reported severity/intensity of ≥4 on a numerical rating scale (0‐10) and signs fulfilling the Research Diagnostic Criteria (RDC/TMD) for disc displacement with reduction. Thirty subjects each were randomised to bite splint, home exercise, or supervised exercise programme at the clinic. Two examiners (authors), blinded to the treatment modality, examined the same subject at baseline and at a 3‐month follow‐up. Non‐parametric statistical methods were applied for analyses. A P‐value <.05 was considered statistically significant. The dropout rate was highest in the home exercise group. About 50% of the participants reported improvement of their TMJ sounds with no significant difference between treatments. In the supervised exercise and the bite splint groups, approximately 2/3 of the patients reported 30% or more improvement of their TMJ sounds and half reported 50% improvement or more. The supervised exercise group also showed reductions in TMD pain, neck disability, mood disturbances and somatisation. Jaw exercise programmes and bite splint treatments had positive effects on TMJ clicking. The supervised exercise programme had an additional effect on the subject's well‐being and thus may help to encourage patient's empowerment and coping strategies.